Passagens da Biblioteca Central ao Centro Cultural São Paulo (1975-1985) - Manzoni, Francis Marcio Alves (2015)
This thesis addresses some dimensions about the creation of the Sao Paulo Cultural Center, since it's idealization as the central library of the state capital, in the second half of the 1970, to a transformation of their original design to house a multidisciplinary cultural institution, opened in 1982 on land adjacent to the subway line, between Avenida 23 de Maio and Rua Vergueiro. Aims to highlight the importance of public spaces as places where culture converges part of relations between citizens and public administration, where they breed unrest within the city because of social inequality and cultural, color, gender and sexuality differences. In this work, the Cultural Center is considered in relation to the city that crosses and their influence on city life. This research sought to recognize the agents involved with the planning of the "new cultural institution", identifying their references and contributions, taking as its starting point the need to expand the Mário de Andrade Library, due to the overcrowding of books in his tower and insufficient space to meet readers and researchers at that institution. It was surveyed the socio-cultural landscape transformations of the city of Sao Paulo in the 1970s and 1980s, the emergence of demands of the population in relation to culture and leisure as well as the development of public policies for culture in this period. Focusing research on the concept of cultural center and its popularity since the late 1970s, this research seeks to contribute to reflection on the culture of public spaces as places of negotiation, of which participated managers related to municipal administration, artists, agencies culture and diverse publics, whose values, identities and interests influence the constitution and functioning of these institutions, much beyond the meanings of art-‐ spectator